2023
DOI: 10.3390/cells12111541
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Photodynamic Therapy with Conjugated Polymer Nanoparticles in Glioblastoma Tumor Microenvironment

Abstract: Alternative therapies such as photodynamic therapy (PDT) that combine light, oxygen and photosensitizers (PSs) have been proposed for glioblastoma (GBM) management to overcome conventional treatment issues. An important disadvantage of PDT using a high light irradiance (fluence rate) (cPDT) is the abrupt oxygen consumption that leads to resistance to the treatment. PDT metronomic regimens (mPDT) involving administering light at a low irradiation intensity over a relatively long period of time could be an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 76 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…Recent advances in PDT-GB research are as follows: (1) coupled NIR and photo immunotherapy (NIR-PIT), where a photosensitizer is conjugated to a highly specific monoclonal antibody [ 1043 , 1044 , 1045 ]; (2) NP-based PDT to augment systemic therapies and avoid skin photosensitization [ 1046 , 1047 ]; (3) NP-based PDT linked to miRNA or other chemotherapeutic agents [ 1048 ]; (4) strategies to increase PDT efficacy in hypoxic TME conditions [ 1049 , 1050 , 1051 , 1052 ]. Although some studies have demonstrated the enhanced penetration of light by simultaneous application of ultrasounds [ 1053 ], combined effects of PDT and SDT did not show any benefit in glioma rat models [ 1054 ].…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%
“…Recent advances in PDT-GB research are as follows: (1) coupled NIR and photo immunotherapy (NIR-PIT), where a photosensitizer is conjugated to a highly specific monoclonal antibody [ 1043 , 1044 , 1045 ]; (2) NP-based PDT to augment systemic therapies and avoid skin photosensitization [ 1046 , 1047 ]; (3) NP-based PDT linked to miRNA or other chemotherapeutic agents [ 1048 ]; (4) strategies to increase PDT efficacy in hypoxic TME conditions [ 1049 , 1050 , 1051 , 1052 ]. Although some studies have demonstrated the enhanced penetration of light by simultaneous application of ultrasounds [ 1053 ], combined effects of PDT and SDT did not show any benefit in glioma rat models [ 1054 ].…”
Section: Non-ionizing Energies In Gb Therapymentioning
confidence: 99%
“…Other than brain tumors, the potential of mPDT has been demonstrated in various other types of cancers, such as colorectal cancer and cervical cancer ( Shi et al, 2019 ; Dai et al, 2023 ) In a study by Caverzán et al, standard and metronomic regimens of conjugated polymer nanoparticles-based PDT was assessed on glioblastoma cell lines and xenograft mouse models. They reported that mPDT regimes induced increased cancer cell death, and lowered therapeutic resistance furthermore resulted in the polarization of one of the most important cancer-related immune cell subtypes, macrophages, towards an anti-tumoral phenotype ( Caverzán et al, 2023 ).…”
Section: More Than Chemotherapy: Metronomic Photodynamic Therapymentioning
confidence: 99%
“…The last literature report cited in the field of PDT supported by conjugated polymer nanoparticles for the treatment of glioblastoma cells is the article by Caverzán et al [ 125 ] from 2023. In this experiment, the authors, starting in 2020, used three glioblastoma cell lines and PDT coupled with polymer nanoparticles.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…This experiment provides information on the development of advanced PDT concepts in conjunction with the application of lower irradiance. The polymer nanoparticles used contribute to the inhibition of tumor growth and initiate subsequent cell death pathways [ 125 ].…”
Section: A Review Of the Literaturementioning
confidence: 99%